The Polarimetric Properties of Fast Radio Burst Emission at Nanosecond Time Resolution - Scott, Danica R. (Curtin University, 2024)
The Australian Square Kilometre Array Pathfinder (ASKAP) is capable of observing fast radio bursts (FRBs; short-duration astronomical radio transients) in great detail, identifying their locations precisely and measuring their signals at the nanosecond level. This thesis develops CELEBI, a software pipeline that has dramatically improved the data processing techniques for producing FRB data products with ASKAP. This thesis presents time-resolved polarisation properties of 21 FRBs obtained with CELEBI and their implications for FRB progenitors.